O PORTUGUÊS BRASILEIRO E AS CONTROVÉRSIAS DA FONÉTICA ATUAL: PELO APERFEIÇOAMENTO DA FONOLOGIA ARTICULATÓRIA - Albano, Eleonora Cavalcante (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The paper examines the recent trends of phonetic studies in Brazil, a productive area which analyses Brazilian-Portuguese data and contributes to phonetic theory. The central question discussed in the approach is the relationship between Phonetic and Phonology. (AE)